JAN PAWEŁ II - PAPIEŻ MEDIÓW. REFLEKSJA PASTORALNO-TEOLOGICZNA - Celary, Ireneusz (Studia Pastoralne, 2023)
John Paul II can certainly be considered an outstanding personality of our time, not merely due to the long duration of his pontificate. He was the first roman pontifex – during the age of mass media – who reached out to the whole world personally, including dissenters as well as infidels. We present here a pastoral-theological review reflecting on the media presence of the deceased pontifex John Paul II, highlighting different aspects of its papacy and providing a theological interpretation. John Paul II didn’t intend to reshape papacy, but did point to different aspects of it. We’d like to assess the changes which resulted from his massive presence in the media additionally to presenting insights in what way the distinct features of his outward appearance in the media can contribute today to make “church as a universal sign” more or less experienceable. The pope from Poland made use of the media like no other pontifex before him leading to the large media attention he received at the end of his life which is unparalleled in history of the Holy See. He enjoyed great appearances and was even selected “Man Of The Year” by Time magazine in 1995.